3-MCPD and glycidol levels in edible oils and fats obtained from local markets in Türkiye - A.O. Gündüz; M.M. Ceylan; A. Baştürk (Grasas y Aceites, 2023)
In this study, it was aimed to determine the 3-MCPD and glycidol levels in 9 types (46 brands) of edible fat and oil offered for sale in markets located in Türkiye. 3-MCPD and glycidol levels were determined by making some modifications to the DGF C VI 18 (10) method. The highest levels of 3-MCPD and glycidol levels were detected in hazelnut oils, riviera olive oils, margarines, and shortenings. As expected, these contaminants were not observed in extra-virgin olive oils, while they were detected at low levels in fish oils. The highest 3-MCPD levels were found in the range of 0.06-2.12 mg·kg-1 in hazelnut oil, 0.16-1.69 mg·kg-1 in riviera olive oils, and 0.17-1.17 mg·kg-1 in margarines. The highest glycidol levels were found in the shortenings in the range of 1.98-6.46 mg·kg-1, followed by hazelnut oil (0.54-2.63 mg·kg-1) and riviera olive oil (0.19-3.53 mg·kg-1).